Evaluation of Microbial Pathogens for Management of Legume Pod Borer, Maruca vitrata F. in Yard Long Bean Ecosystem - Ahmed, RN; Uddin, MM; Haque, MA; Ahmed, KS (International Journal of Applied Sciences and Biotechnology, 2020)
Bean pod borer, Maruca vitrata is a serious pest of bean which causes serious yield loss of bean and other leguminous crops. To evaluate the field efficacy of two microbial pathogens for the management of legume pod borer, Maruca vitrata F an experiment was carried out in the field laboratory of the Department of Entomology, Bangladesh Agricultural University (BAU), Mymensingh during kharif season in 2016 on yard long bean plants. Entomopathogens viz. Bacillus thuringiensis and Beauveria bassiana were used @ 0.50, 1.00 & 1.50 g/L and 0.25, 0.50 & 0.75 g/L, respectively to conduct the experiment. These two entomopathogens showed significant effect on the management of bean pod borer in comparison to untreated control in the field in decreasing the flower (22.02, 29.72, 33.35% and 16.16, 24.26, 30.05% by Bt & Bb, respectively) and pod infestation (16.45, 25.69, 31.93% and 10.73, 21.57, 28.04% by Bt & Bb, respectively). These two pathogens showed a significant effect on the yield with increasing pod yield 10.65, 20.32, 26.25% and 7.69, 14.58, 21.79% by Bt & Bb, respectively of yard long bean. Besides, these both the two entomopathogens were almost similar to the effect of a widely used chemical insecticide Nitro 505 EC in managing pod borer in the field. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 199-204